Nathaniel Silsbee papers - Silsbee, Nathaniel, 1773-1850.
Chiefly letters written by Silsbee relating to Massachusetts and national politics. Correspondents include James Trecothick Austin, Lewis Brantz, Thomas P. Coxe, H. A. S. Dearborn, Mahlon Dickerson, David Henshaw, James Miller, James Kirke Paulding, David Porter, Samuel L. Southard, Smith Thompson, and Bryant P. Tilden
U.S. representative and senator from Massachusetts, shipowner, and banker.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Austin, James Trecothick, -- 1784-1870 -- Correspondence; Brantz, Lewis -- Correspondence; Coxe, Thomas P. -- Correspondence; Dearborn, H. A. S. -- 1783-1851 -- Correspondence; Dickerson, Mahlon, -- 1770-1853 -- Correspondence; Henshaw, David, -- 1791-1852 -- Correspondence; Miller, James, -- 1776-1851 -- Correspondence; Paulding, James Kirke, -- 1778-1860 -- Correspondence; Porter, David, -- 1780-1843 -- Correspondence; Southard, Samuel L. -- 1787-1842 -- Correspondence; Thompson, Smith, -- 1768-1843 -- Correspondence; Tilden, Bryant P. -- 1817-1859 -- Correspondence; Massachusetts -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1783-1865.; Bankers; Representatives, U.S. Congress -- Massachusetts; Senators, U.S. Congress -- Massachusetts; Shipowners